The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/mrm.1910320315
|View full text |Cite
|
Sign up to set email alerts
|

Thin film high temperature superconducting RF coils for low field MRI

Abstract: We have built and tested a thin-film high temperature superconducting (HTS) surface coil for MRI at 0.064T. When placed as close as possible to a conductive sample, the 6.7-cm outer diameter HTS coil had a measured signal-to-noise ratio (SNR) 1.8 times higher than a room temperature copper coil of similar size and location. Our results predict that in some cases, SNR gains of about a factor of 2 can be attained in low-field MRI systems by substituting HTS surface coils for copper coils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…In light of the operating characteristics documented above, we evaluated the Helmholtz HTS probes in terms of surface coil probes demonstrated by other investigators (3,(6)(7)(8)21). The largest gains to date were reported by Black et al (7,8) who demonstrated a ϳ10ϫ gain in SNR when comparing coils of identical geometry.…”
Section: Comparison With Prior Hts Probesmentioning
confidence: 96%
See 2 more Smart Citations
“…In light of the operating characteristics documented above, we evaluated the Helmholtz HTS probes in terms of surface coil probes demonstrated by other investigators (3,(6)(7)(8)21). The largest gains to date were reported by Black et al (7,8) who demonstrated a ϳ10ϫ gain in SNR when comparing coils of identical geometry.…”
Section: Comparison With Prior Hts Probesmentioning
confidence: 96%
“…As the size of a sample decreases, the thermal noise of the receiver coil starts to represent a greater proportion of the total system noise, and eventually a point is reached where the coil rather than the sample determines the SNR at the preamplifier (1,2). In an effort to limit receiver coil noise for both small sample and low magnetic field applications, a number of investigators have reported the use of high temperature superconducting (HTS) materials in the construction of low-noise radiofrequency (RF) coils (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to gain more signal in low-field imaging would be the development and use of superconducting surface coils for signal detection, which lead to a two-or threefold increase in signal-to-noise ratio [21]. This could be used either for a significant reduction in imaging time or for gaining more in-plane resolution.…”
Section: Image Qualitymentioning
confidence: 99%
“…[11] By introducing the signal voltage V match at the input of the preamplifier when the coil is matched, we may rewrite Eq.…”
mentioning
confidence: 99%